Operational Efficiency of CapEx Procurement: The Impact of Lead Time and Requisition Quantity on Delivery Performance - Chowdhury, Md. Hasan Maksud; Khan, Md. Rashad Yaqub (ExcelingTech, 2025)
A large number of lifestyle brands, such as Aarong, Yellow, Cats Eye, etc., are driving the apparel market of Bangladesh. Within this market, a huge number of capex procurements are required annually to meet companies' requirements. Each completed requisition includes a lead time, which is a critical factor impacting overall operational efficiency. This study determines the impact of the metrics, requisition quantity, and lead time on delivery performance. The purpose of the study was to discover the relationship between key variables that ease decision making and to establish the development of a concrete knowledge base intended to support strategies for managing diverse requisition quantity and lead time. Consequently, the study served the purpose of improving supply chain efficiency. To discover the relationship, supply chain and procurement theories were addressed. A total of 8,099 procurement records were analysed through the lens of a positivist research paradigm to ensure objectivity. A quantitative method was employed to conduct tests that generate accurate results supporting the purpose of this study. Predictions for the test were formulated to develop connection between lead time, requisition quantity on delivery performance. Chi-square tests were carried out to find out the connection. Findings revealed that the lead time and requisition quantity had a significant impact on delivery performance. Altogether, the study contributes to procurement and supply chain management literature by presenting evidence-based analysis into how operational factors and distinct item types may affect delivery efficiency.